Community Acceptance and Utilization of Maternal and Community-Based Neonatal Care Services Provided by Health Extension Workers in Rural Sidama Zone: Barriers and Enablers: A Qualitative Study - Gebretsadik A; Melaku N; Haji Y (Dove Medical Press, 2020)
Achamyelesh Gebretsadik,1 Nebiyu Melaku,2 Yusuf Haji1 1School of Public Health, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia; 2Maternal and Child Health Core Process, Southern Nation Nationalities and People Regional Health Bureau, Hawassa, EthiopiaCorrespondence: Achamyelesh GebretsadikSchool of Public Health, College of Medicine and Health Sciences, Hawassa University, PO Box 46, Hawassa, EthiopiaTel +251 911303128Email agtsadik@gmail.comPurpose: This study assessed the community acceptance and utilization of maternal and community-based neonatal care services, its barriers, and enablers in southern Ethiopia, 2019.Methods: An exploratory qualitative study was conducted among mothers, health extension workers, their supervisors and coordinators in four districts of Sidama Zone, Hawassa University Demographic Surveillance Site. An in-depth interview has been carried out with eight health extension workers and eight program coordinators and supervisors, while four focus group discussions were held with eligible mothers. Digital recording was applied to record the interview and discussion followed by transcription and thematic analysis through open code.Results: Study findings reveal that services provided by health extension workers at community level for mothers and their children are highly appreciated and recognized by the community. Most of the communities are free from wrong perception regarding the practices. Their performance was better in focused antenatal care, but postnatal care and community-based neonatal care were reported to be insignificant. Knowledge and skills of HEWs was based on their extended experiences. The challenges and opportunities include workload, road inaccessibility, poor supervision, inadequate drugs and equipment supply, shortage of man power and budget at health posts, distance and topography factors of homes from health posts making the visits more difficult, etc. To improve uptake of the services, increasing the number of health extension workers in the heath post, supportive supervision, continuous essential drugsm and medical supplies were suggested by participants.Conclusion: This study shows that services provided by health extension workers for mothers and their neonates are highly appreciated by the community, and there is better change in focused antenatal care services, but postnatal care and sick newborn care are still low. Therefore, maternal and neonatal programs should focus on the postnatal home visits and sick newborn care through solving identified barriers.Keywords: knowledge of HEWs, community-based neonatal care, performance, improvement, Sidama, Ethiopia